2015
DOI: 10.1039/c4ra07351g
|View full text |Cite
|
Sign up to set email alerts
|

Over-activity and stability of laccase using ionic liquids: screening and application in dye decolorization

Abstract: The use of a wide range of water miscible and immiscible ionic liquids (ILs) as reaction media for ABTS (2,2′-azino-bis(3ethylbenzothiazoline-6-sulfonic acid) diammonium salt) oxidation by Trametes versicolor laccase was studied. Thirteen ILs were shown to be suitable media for the laccase oxidation reaction, increasing the activity with respect to conventional media. Among them, the water-miscible IL choline dihydrogen phosphate [Chol][H 2 PO 4 ] allowed over-laccase activity with an enhancement rate of 451% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 53 publications
3
47
0
Order By: Relevance
“…The value of n indicates the type of isotherm to be favorable (n > 1), unfavorable (n < 1), linear (n = 1). The high values of n (n > 2) at equilibrium at all 10 the temperature conditions indicated that biosorption of the dyes onto the CATCA flocculant were favorable processes. Temkin isotherm and the R-P isotherm constants and the correlation coefficients are listed in Table S1-S4 (in supporting information).…”
Section: Adsorption Isothermmentioning
confidence: 99%
See 4 more Smart Citations
“…The value of n indicates the type of isotherm to be favorable (n > 1), unfavorable (n < 1), linear (n = 1). The high values of n (n > 2) at equilibrium at all 10 the temperature conditions indicated that biosorption of the dyes onto the CATCA flocculant were favorable processes. Temkin isotherm and the R-P isotherm constants and the correlation coefficients are listed in Table S1-S4 (in supporting information).…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…According to Chiou and Yoshida 27 charge dominates the surface of CATCS and strong electrostatic attraction exists between the positively charged surface of CATCS and negatively charged dyes. As the pH increased, the positive charge on CATCS reduced which made electrostatic attraction force decline and the existence of excess OHions will 10 compete with dye anions for the adsorption sites 29 , therefore prevented the adsorption of dye anions on the adsorbent surface.…”
Section: Effect Of Initial Ph On Decolorization Efficiencymentioning
confidence: 99%
See 3 more Smart Citations